Type II endometrial cancers: A case series - Flora D Lobo; Eliz Thomas (Wolters Kluwer Medknow Publications, 2016)
Introduction: Endometrial carcinoma ranks 3rd in India among gynecological malignancies. Endometrial cancer (EC) can be classified into two distinct groups - type I and type II, based on histology, which differs in molecular, clinical and histopathological profiles. Type II is nonestrogen dependent, nonendometrioid, more aggressive and carries poor prognosis. Although type II cancers contribute only about 10% of EC incidence, they present at advanced age and cause approximately 50% recurrence and deaths with a low 5-year, overall survival rate. Type II EC are also characterized by genetic alterations in p53, human epidermal growth factor-2/neu, p16 and E-cadherin. Materials and Methods: Endometrial carcinomas diagnosed from endometrial biopsies and hysterectomy specimens received in the Department of Pathology, Kasturba Medical College, Mangalore, from January 2007 to June 2012 were included in the study. Clinicopathological analysis of the 84 cases of EC was done with emphasis on morphology. p53 immunostaining was performed in two cases of serous carcinoma. Results: Out of a total of 84 cases of EC, ten cases were of type II (11.9%). Out of which, eight were serous carcinoma (9.5%) and two clear cell (2.4%). p53 immunostain was strongly positive in the serous papillary carcinomas. The age of the patients ranged from 45 to 75 years. Myometrial invasion was more than half. Treatment was hysterectomy followed by aggressive chemotherapy. Conclusion: Of the type II EC, serous carcinoma is the most common type. Clinical presentation and prognosis differs in comparison to type I EC, thus the recognition of this type of EC is pivotal.